The Utilization of 3D Technology in Mathematics Learning - Didik Iskandar; Ilmiyati Rahayu; Uyung Amilul Ulum; Lukmanul Hakim; Yayat Ruhiya (Postgraduate, University of Mataram, 2023)
The development of information and communication technology in Indonesia has developed very rapidly. This can be seen in smartphone users, the number of bloggers in Indonesia, Facebook or other social media users, and internet users. One of the information and communication technologies that is starting to develop in Indonesia is Virtual Reality. This technology in Indonesia is still not much developed. Virtual Reality technology that has entered Indonesia is mostly only in the form of games. There are not many Virtual Reality developers in Indonesia. The Indonesian government itself is currently promoting the digitization of school (learning) materials, one of which is through the Electronic Book Series from the Ministry of Education and Culture for elementary school, junior high school high school and vocational school children. Electronic Series Books are still limited to masters or digitalized books, while the development of Virtual Reality in the education sector in Indonesia is still not large and has not yet developed. In Indonesia, almost no elementary schools utilize Virtual Reality technology in their learning process and mathematics is one of the school materials that is very feared by students, apart from English and regional languages ​​(Javanese). From the above background, researchers developed a mathematics learning application for the elementary school level based on Virtual Reality technology. With this Virtual Reality technology, children are invited to play and learn so that children are able to work on math problems in a fun way